Matsumoto Shigeharu bearing witness - Kaimai, Jun 1957- (international library selection)
Shigeharu Matsumoto (1899-1989) was brought up in Osaka. He studied law and English at Tokyo University before going in 1923 to the USA to study economics and history at Yale. He went on to Europe in 1925, where he interpreted for Japanese delegates at an ILO conference in 1926. His ambition of becoming a professional journalist was fulfilled when he was appointed as the head of the Shanghai bureau of the Rengo (later Domei) news agency. In 1936 his reporting of the Xi?an incident was a news scoop which marked him out as a well-connected and influential journalist and brought him into contact with Japanese leaders including Fumimaro Konoe. Shigeharu Matsumoto was a well-known internationalist with many friends outside Japan including politicians, journalists and diplomats. He is particularly remembered as the founder and developer of the International House of Japan in Roppongi in Tokyo which with its seminar rooms, library and accommodation for scholars has contributed so much to exchanges between Japanese and foreign scholars. But he was much more than a major participant in international exchanges. He was an influential journalist who was able to view from his post as correspondent of Rengoand later of Domei the course of Japan?s war in China with its tragic consequences for Japan as well as for China. He was an active participant in the internationalization of Japan in the latter part of the twentieth century. -- from http://www.japansociety.org.uk (Oct. 22, 2015).10